Legal Analysis of Fintech: The Role of Law in Facing the Era of Technological Disruption - Wardani, Rahmawati Mayta (Kopertais Wilayah I DKI Jakarta dan Banten, 2023)
Fintech is a company that focuses on creating innovations in the field of financial services with the help of contemporary technology Fintech helps the sales process become more common. The emergence of new business models such as Fintech, increasing cybersecurity risks, changing consumer behavior, and limited access to finance are the main challenges facing the banking industry today. The era of disruption is a state when innovation, technology, and social change significantly disrupt or transform businesses, industries, and the way people live. This research is expected to help solve the problems of how the current legal framework accepts diverse and new Fintech business models and how Fintech consumer education and literacy efforts can be improved to minimize risks and increase awareness of their rights. This research collected data and information from various secondary sources, including news reports and legal documents. Through qualitative analysis using normative methods, this article also highlights the importance of a clear and comprehensive legal role for new business models, strengthening cybersecurity regulations, supporting technological innovation and development, and increasing financial inclusion. Thus, the banking industry can utilize technology to improve services, expand outreach, To encourage the healthy growth of the Fintech industry and benefit society at large, the law must be flexible and responsive to technological developments and new business models in this sector. This legal analysis of fintech aims to provide a comprehensive understanding of the various legal issues that arise in this era of technological disruption.